Above ground carbon biomass assessment using satellite remote sensing reflection values - Uttaruk, Yannawut; Rotjanakusol, Tanutdech; Laosuwan, Teerawong (Food Agricultural Sciences and Technology, 2018)
This research focused on the estimation of above ground carbon biomass of orchards in Sang Kho Sub-District, Phu Phan District, Sakon Nakhon Province in the northeast of Thailand using remote sensing with Modified Soil Adjusted Vegetation Index-2 (MSAVI2) and Fractional Vegetation Cover (FVC). The study methodology was conducted by bringing data from Landsat 8 OLI to adjust the reflection of the Top of Atmosphere (ToA) and classify the vegetation by using MSAVI2. Pixel values above 0-1 were determined to be vegetation and pixel values equal to or below 0 were determined not to be vegetation. Then, the pixel value was determined to classify the vegetation to be 0-100 by using FVC and the satellite data obtained from the previous process was applied to determine the correlation with the field data by statistical methods to get the correlation equation y = 0.0874e0.064x with a coefficient of determination R² = 0.9123. The calculation resulted in an above ground carbon content of 277.430 tCO2 /rai. In addition, the researchers also tested the statistical accuracy of the above ground carbon, which could be analyzed by Landsat 8 OLI and field data with a Paired Sample T-test. The result found no statistically significant difference at a confidence level of 95%.